The Chimeric Adenovirus (Ad5/35) Expressing Engineered Spike Protein Confers Immunity against SARS-CoV-2 in Mice and Non-Human Primates - Seung-Phil Shin; Kwang-Soo Shin; Jeong-Mi Lee; In-Kyung Jung; Jimo Koo; Seung-Woo Lee; Seowoo Park; Jieun Shin; Myunghwan Park; Bongju Park; Hanseul Oh; Bon-Sang Koo; et al. (Vaccines, 2022)
Several COVID-19 platforms have been licensed across the world thus far, but vaccine platform research that can lead to effective antigen delivery is still ongoing. Here, we constructed AdCLD-CoV19 that could modulate humoral immunity by harboring SARS-CoV-2 antigens onto a chimeric adenovirus 5/35 platform that was effective in cellular immunity. By replacing the S1/S2 furin cleavage sequence of the SARS-CoV-2 Spike (S) protein mounted on AdCLD-CoV19 with the linker sequence, high antigen expression was confirmed in various cell lines. The high levels of antigen expression contributed to antigen-specific antibody activity in mice and non-human primates (NHPs) with a single vaccination of AdCLD-CoV19. Furthermore, the adenovirus-induced Th1 immune response was specifically raised for the S protein, and these immune responses protected the NHP against live viruses. While AdCLD-CoV19 maintained neutralizing antibody activity against various SARS-CoV-2 variants, it was reduced to single vaccination for β and ο variants, and the reduced neutralizing antibody activity was restored with booster shots. Hence, AdCLD-CoV19 can prevent SARS-CoV-2 with a single vaccination, and the new vaccine administration strategy that responds to various variants can maintain the efficacy of the vaccine.